2010
DOI: 10.1590/s1516-89132010000300028
|View full text |Cite
|
Sign up to set email alerts
|

Effect of inclusion of citrus pulp in the diet of finishing swines

Abstract: The aim of this work was to study the effect of inclusion of citrus pulp in the diet

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
11
1
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 15 publications
5
11
1
2
Order By: Relevance
“…Its inclusion at levels up to 150 g/kg in finishing pig diets showed effects on nutrient digestibility reducing GE and increasing NDF-and ADF-CTTAD; however, the digestibility of GE was acceptable up to 100 g inclusion/kg of diet. These results are in agreement with those reported in the literature (Baird et al, 1974;Galassi et al, 2004;Watanabe et al, 2010a;Ruiz et al, 2012) in which the inclusion of dried citrus pulp or other pectinrich feedstuff such as sugar beet pulp lowered nitrogen (N) and EE digestibility but significantly increased fibre digestibility. Also Rijnen et al (2001) found increased fibre digestion in sows fed diets with sugar beet pulp silage.…”
Section: Digestibility and Performancesupporting
confidence: 92%
See 3 more Smart Citations
“…Its inclusion at levels up to 150 g/kg in finishing pig diets showed effects on nutrient digestibility reducing GE and increasing NDF-and ADF-CTTAD; however, the digestibility of GE was acceptable up to 100 g inclusion/kg of diet. These results are in agreement with those reported in the literature (Baird et al, 1974;Galassi et al, 2004;Watanabe et al, 2010a;Ruiz et al, 2012) in which the inclusion of dried citrus pulp or other pectinrich feedstuff such as sugar beet pulp lowered nitrogen (N) and EE digestibility but significantly increased fibre digestibility. Also Rijnen et al (2001) found increased fibre digestion in sows fed diets with sugar beet pulp silage.…”
Section: Digestibility and Performancesupporting
confidence: 92%
“…In the present study, digestible protein of ECP was low (33.8 g/kg of DM), but this was expected since the mean CP content of citrus by-products is generally low and often linked to fibre (Gasa et al, 1992). On the other hand, Watanabe et al (2010a) reported digestible protein contents even lower for dried citrus pulp (8.9 g/kg of DM), thus indicating that the ensiling process could increase the availability of the inherent low digestible protein of fruits. Overall, in terms of nutritive value, ECP seems a low valuable feedstuff in pig nutrition.…”
Section: Carcass Qualitymentioning
confidence: 50%
See 2 more Smart Citations
“…In relation to diets containing citrus pulp, the reduction in daily feed intake, the worse weight gain and feed conversion can be justified by low palatability of the ingredient to swine, as stated by Watanabe et al (2010) when using citrus pulp in the diets of finishing pigs.…”
Section: Assaymentioning
confidence: 99%